A novel clinical and cardiac magnetic resonance risk score for early risk prediction after ST-segment elevation myocardial infarction. (3rd October 2022) - Marcos Garces, V; Perez, N; Gavara, J; Lopez-Lereu, M P; Monmeneu, J V; Rios-Navarro, C; De Dios, E; Merenciano-Gonzalez, H; Gabaldon-Perez, A; Chorro, F J; Valente, F; Lorenzatti, D; et al.
Abstract: Background: Cardiac magnetic resonance (CMR) performed early after ST-segment elevation myocardial infarction (STEMI) can improve major adverse cardiac event (MACE) risk prediction. However, predictive models including clinical and CMR variables are scarce and not routinely implemented in clinical practice. Purpose: We aimed to create a simple clinical-CMR risk score for early MACE risk stratification in STEMI patients. Methods: We performed a multicenter prospective registry in three Spanish university hospitals of reperfused STEMI patients (n=1118) in whom early (1-week) CMR-derived left ventricular ejection fraction (LVEF), infarct size and microvascular obstruction (MVO) were quantified. MACE was defined as a combined clinical endpoint of cardiovascular (CV) death, non-fatal myocardial infarction (NF-MI) or re-admission for acute decompensated heart failure (HF), whichever occurred first. Univariate and multivariate analyses were performed and a risk score was computed using the variables which independently predicted the risk of MACE. Results: During a median follow-up of 5.52 [2.63–7.44] years, 216 first MACE (58 CV deaths, 71 NF-MI and 87 HF) were registered. Mean age was 59.3±12.3 years and most patients (82.8%) were male. Based on the four variables independently associated with MACE, we computed an 8-point risk score: time to reperfusion >4.15h (1 point), GRACE risk score >155 (3 points), CMR-LVEF <40% (3 points), and MVO >1.5 segments (1 point). This score permitted MACE risk stratification: MACE per 100 person-years was 1.96 in the low-risk category (0–2 points), 5.44 in the intermediate-risk category (3–5 points), and 19.7 in the high-risk category (6–8 points): p<0.001 in multivariable Cox survival analysis. Conclusions: A novel risk score including clinical (time to reperfusion >4.15h and GRACE risk score >155) and CMR (LVEF <40% and MVO >1.5 segments) variables allows for simple and straightforward MACE risk stratification early after STEMI. External validation should confirm the applicability of the risk score. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Instituto de Salud Carlos III and Fondo Europeo de Desarrollo Regional (FEDER) and Sociedad Española de Cardiología.